Fiscal policy in China (1949-2019) - Yang, Zhiyong (Researcher of finance) (Routledge, 2026)
"This book offers a comprehensive analysis of the evolution of China's fiscal policy since 1949. It provides an in-depth understanding of the contextual factors that shape its implementation and examines the transition logic between planned fiscal policy and market-oriented fiscal approaches. The author introduces fiscal policy focused on national economic recovery (1949-1952), planned fiscal policy (1953-1977), fiscal policy adapted to economic transition (1978-2011), and fiscal policy in the new era (2012-present). With "fiscal balance" as the central theme, he summarizes the fundamental principles and key dynamics underpinning China's fiscal policy and presents a clear framework for understanding the evolution and strategic rationale behind the country's approach to fiscal governance. The title will appeal to scholars of Chinese economy, comparative economics, public finance, and macroeconomics"-- Provided by publisher.
Keywords: Fiscal policy -- China -- History -- 20th century.; Fiscal policy -- China -- History -- 21st century.; China -- Economic policy -- 1949-; elektronické knihy; electronic books